Bioethanol production from CO-gasification of lignocellulosic biomass and charcoal - Monir, Md. Minhaj Uddin (2019)
Global energy demand is increasing due to rapid industrialization and urbanization. Moreover, augmented consumptions of fossil fuels make the global energy demand critical. So, to meet up the future energy demand an alternative approach is mandatory. The present study emphasizes on the valorization of mostly available renewable energy resources of lignocellulosic biomass (empty fruit bunch of palm oil, forest residue and coconut shell) and its by-product (charcoal) for the production of syngas and bioethanol through the hybrid process of thermo-chemical (co-gasification of feedstocks to syngas) and biochemical (microbial fermentation of syngas), respectively. The physiochemical characterization of feedstocks was performed to find out their bioenergy potentiality. The simulation model was carried out to obtain an optimum condition for co-gasification based on some assumptions using Aspen Plus® (V 8.6) under variable operating conditions (air flow rate, moisture content and composition of the feedstock). Then various mixtures of biomass with charcoal (0-40%) were co-gasified in a downdraft gasifier (DG) for syngas production. The controlling factors (i.e., temperature, pressure) of the reactor were evaluated on various parameters namely heating value, syngas yield, cold gas efficiency, carbon conversion efficiency, exergy efficiency and syngas composition to verify the production of syngas during the co-gasification process with air (~35 m3h−1). Subsequently, syngas fermentation was performed using a TFB bioreactor, and bioethanol production was investigated considering various effects (syngas impurity, temperature, pH, colony forming unit, total organic carbon, syngas composition). The initial yield of syngas was characterized by Gas chromatography-thermal conductivity detector and the ultimate yield of bioethanol was identified by Gas chromatography-mass spectrometry and Nuclear magnetic resonance (1H) analysis. Morphological analysis of this study reveals that in terms of gasification, higher cellulose and hemicellulose containing biomass is better than the charcoal. The concentration variation of the downdraft reactor showed that the CO and H2 concentration increase with the increasing charcoal (up to 40%) with increasing temperature (800-1000°C) and pressure (25-35bar). On the contrary, an opposite trend for the case CO2 concentration was observed with increasing the charcoal in the reactor. However, CH4 concentration was relatively unchanged throughout the reactions of several co-gasification ratios. Consequently, the optimal yield of syngas (H2:CO) ratio for three different co-gasification was found to be 1.10-1.55 after the biomass:charcoal mixture of 70:30 and 60:40 w/w for maximizing the benefits of the gasification process. Successively, the concentration of bioethanol production using yeast (Saccharomyces cerevisiae) and bacteria (Clostridium butyricum) were 15.28 mmol/L and 14.97 mmol/L, respectively. Thus, the available lignocellulosic biomass of EFB, FR and CS with by-product charcoal could be suited for co-gasification for syngas production, and further, it is also suited for the conversion of bioethanol through syngas fermentation using Saccharomyces cerevisiae and Clostridium butyricum. This research may contribute to affordable and environment-friendly syngas and bioethanol-based energy and to reduce the dependency on limited fossil-based fuels.